Handheld XRF Analysis of Ancient Pottery From Bethsaida, Israel - Lenard, Lucas; Schreiber, Mitch; Carlson, Bailey; Luczak, Jonathan (My University, 2015)
This study analyzes 32 pottery sherds from the Bethsaida dig site and compares their compositions to previously tested pieces from the site.
Color poster with text, photographs, tables, and images.
Keywords: Archaeology; Israeli pottery; X-ray fluorescence (XRF); Posters